2018
DOI: 10.1093/jn/nxy153
|View full text |Cite
|
Sign up to set email alerts
|

Cooking Conditions Affect the True Ileal Digestible Amino Acid Content and Digestible Indispensable Amino Acid Score (DIAAS) of Bovine Meat as Determined in Pigs

Abstract: Cooking conditions affect the true ileal digestible amino acid content and DIAAS of beef, as determined with the use of the pig model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 23 publications
6
31
1
Order By: Relevance
“…Consequently, complementing cereal-based diets with higher-quality proteins may overcome IAA deficiencies. The excellent quality of dairy proteins was demonstrated by Rutherfurd et al (3) and Mathai et al (4) , and high DIAAS for beef cooked to an internal temperature of 71°C was reported by Hodgkinson et al (7) . Meat can be prepared by various techniques and to different degrees of doneness, but to our knowledge, there have been no studies conducted to determine DIAAS for meat that have undergone extensive processing (i.e.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…Consequently, complementing cereal-based diets with higher-quality proteins may overcome IAA deficiencies. The excellent quality of dairy proteins was demonstrated by Rutherfurd et al (3) and Mathai et al (4) , and high DIAAS for beef cooked to an internal temperature of 71°C was reported by Hodgkinson et al (7) . Meat can be prepared by various techniques and to different degrees of doneness, but to our knowledge, there have been no studies conducted to determine DIAAS for meat that have undergone extensive processing (i.e.…”
Section: Discussionmentioning
confidence: 90%
“…Hodgkinson et al (7) reported DIAAS for beef from 80 to 99 as evaluated in the growing pig. Raw beef and roasted beef were reported with a DIAAS of 97 and 91, respectively (7) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations